Formula prebiotik berbasis pangan lokal dapat meningkatkan z-skor PB/U pada anak stunting - Edy Waliyo; Shelly Festilia Agusanty; Didik Hariyadi (AcTion: Aceh Nutrition Journal, 2020)
Stunting occurs in a chronic small intestinal inflammation syndrome, called pediatric environmental enteropathy, resulting in increased intestinal permeability and the entry of immune cells into the intestinal epithelium. The purpose of this study was to study the types of prebiotic food formulas and their effects on LAZ in stunting children. This type of research is a quasi-experimental design with a pretest-posttest control group design. Held in Sei Ambawang District, Kubu Raya Regency 2019. Samples of stunting children aged 12-24 months were 40 children. The sampling technique was used for purposive sampling. The intervention given is prebiotic formula food given for 30 days. Data processing for LAZ, nutrient intake, and t-independent test statistical analysis each using WHO Anthro 2005, Nutri survey, and SPSS software. The results showed there were differences in LAZ before and after in the group given MF-2 food formula in stunting children (p= 0,034), whereas in the group who received MF-1 showed no difference (p= 0,114). Based on LAZ differences between the two groups after the intervention with independent t-test did not show significant differences (p > 0,05). In conclusion, MF-1 and MF-2 did not differ in increasing LAZ in stunting children, but each group showed MF-2 had an effect on increasing LAZ.